The Region of Metlaoui Facing Seismic Hazards: Study and Cartographic Approach (South Atlas of Tunisia) - Aliouet, Slim; Melki, Fetheddine (International Journal of Geography and Geology, 2022)
The region of Metlaoui (South Atlas of Tunisia) is listed as one of the major seismotectonic zones of the national territory. About 10 major seismic events with moderate magnitude have occurred from the beginning of last century. The event of 7/11/1989 (Ms = 4.4) was undoubtedly the most important. It caused very significant material damage estimated at 224,525,000 Tunisian Dinars. This study uses a mapping tool to define areas with relatively high degrees of hazard and vulnerability. It also seeks to understand the active fault of the seismic events recorded in this region.